Proposing Notaries’ Deed Digitalization in Indonesia - Agustin, Ika Yuli; Anand, Ghansham (Lentera Hukum, 2021)
Along with emerging technology, a notary public's role should adjust this changing development, mainly dealing with a deed. Technological development inevitably impacts the role of a notary public and the future digitization of notarial deeds. To date, notaries in Indonesia remain implementing laws and regulations that have not been changed. In contrast, technological development has shifted rapidly, especially on the notaries' task in appearing, reading, signing, and using stamps. This study aimed to identify the challenges of implementing notaries’ deed digitalization by taking into account rapid technological development. With legal research, this study showed that as a consequence of technological development, notarial functions’ disruption in Indonesia evoked a concept of a cyber notary, an idea of notarial function through an online system. As it has flourished globally, digital disruptions had brought out an electronic system that changed the implementation of works, business, professions, and functions, mainly to notarial functions. Nevertheless, no specific rules were established to amend Notary Law 02/2014, particularly to the requisites of authentic deeds by a cyber notary. Indonesia applied some restrictions on technology to maintain the legality of authentic deeds to place the notarial profession as a public official consistently. KEYWORDS: Indonesian Notaries, Technological Development, Deed Digitalization.